The Black worker during the era of the Knights of Labor - Foner, Philip Sheldon, 1910-1994; Lewis, Ronald L., 1940-; Ervin, Keona K. (Black worker ;, 2019)
"The documents that make up volumes three and four show the centrality of Black unionism to the debates about labor and capital that profoundly shaped national politics in the late nineteenth and turn of the twentieth centuries. They include, for example, the testimony of Black workers to the 1883 Senate Committee on Relations between Labor and Capital and debates within the Knights of Labor about whether Black workers were influential political participants. The formation of the Knights and Black workers' organizing in the South is told through New Orleans local papers such as the Picayune and Weekly Louisianian. Also noteworthy are Frederick Douglass' address to the National Convention of Colored Men in Louisville, Kentucky and the work of writers who crafted editorials for the New York Freeman, New York Age, and AME Church Review. The proceedings of Knights of Labor conventions are found in local and national papers, the papers of Knights leader Terrence V. Powderly, and excerpts from his account, Thirty Years of Labor (1889). The Colored Farmers' National Alliance, a crucial organization that inserted Black farmers into the white-dominated and racially exclusive or discriminatory "southern alliances" such as the Farmers' alliance and the Populist or People's Party, holds a prominent place"--From Foreword.